Tyranny of the Majority Reflected in Henrik Ibsen's An Enemy of the People Drama (1882): A Sociological Approach - Hananto, Mohamad, Tegar, Dr. Phil. Dewi Chandraningrum, M. Ed, Titis Setyabudi, S.S. M. Hum (2015)
The research is proposed to analyze the social aspects in An Enemy of the People drama. The major problem in this article is to explain how the social problem reflected in An Enemy of the People drama. The object of the study is An Enemy of the People drama written by Henrik Ibsen. Qualitative study is a method which is used to analyze the sociological aspects reflected in the drama. The result of this study is Henrik Ibsen shows the social condition of Norway. Although Norway in nineteenth century was including progressive country, Henrik Ibsen also criticized the government for controlling the society and ruling as the majority to the minority. Key word: Social Aspects, An Enemy of the People, Sociological approach.